Passive & active RF-microwave circuits course and exercises with solutions - Jarry, Pierre 1946-; Beneat, Jacques 1964- (ISTE Press Ltd, 2015)
Microwave and radiofrequency (RF) circuits play an important role in communication systems. Due to the proliferation of radar, satellite, and mobile wireless systems, there is a need for design methods that can satisfy the ever increasing demand for accuracy, reliability, and fast development times. This book explores the principal elements for receiving and emitting signals between Earth stations, satellites, and RF(mobile phones) in four parts; the theory and realization of couplers, computation and realization of microwave and RF filters, amplifiers and microwave and RF oscillators. Passive & Active RF-Microwave Circuits provides basic knowledge for microwave and RF range; each chapter provides a complete analysis and modelling of the microwave structure used for emission or reception technology, providing the reader with a set of approaches to use for current and future RF and microwave circuits designs